Weed communities of Jerusalem artichoke (Helianthus tuberosus L.) cultivation - Stachurska-Swakoń, Alina; Rakowska, Rita; Klich, Sabina (Annales Universitatis Paedagogicae Cracoviensis Studia Naturae, 2022)
Jerusalem artichoke could be used as a source of renewable energy in the meaning of biomass combustion or liquid fuels production. The presented study concerned on the impact of JA plantation for biomass combustion on plant diversity. The spontaneous vegetation of JA crops studied on the basis of phytosociological methods consisted of varied groups of species that contain weeds (32%), meadow (29%), and ruderal (13%) species. Most of the species occurred sporadically (55%) with low frequency. Most of the plants accompanying JA cultivation were perennial, mainly hemicryptophytes (51%) with a smaller number of geophytes (17%). Therophytes constituted 25% of spontaneous flora of JA crops. It can be proposed the group of generalist energy crop weeds with Convolvulus arvensis, Elymus repens, Equisetum arvense, Ranunculus repens, and Rumex obtusifolius.